PERAN MAMAK KANDUANG DALAM STRUKTUR KELUARGA MINANG DI PERANTAUAN (Studi Kasus: Persatuan Keluarga Silungkang) - Fatimah Az-zahroh; Meila Riskia Fitri (Program Studi Sosiologi, FISIP ULM, 2023)
This study aims to describe the existence of mamak kanduang in the Minangkabau family structure and to describe the role of mamak kanduang in the family structure of the five members of the Silungkang Family Association. This study uses Bruce Biddle's role theory in analyzing the phenomena that occur. The results of this study indicate that adult Minang men have two linear roles, namely being a father as well as being a mamak. In the nuclear family, a Minang man will play the role of father, while in his mother's family he will play the role of mamak to his nephew (child of his sister). The role of the father in the nuclear family in Nagari Silungkang is to raise a child, and then this role will be transferred to the mother if the child reaches the ripe age to marry. In the Silungkang village, the role of the mamak kanduang is to look after the welfare of the family and to be responsible for the arranged marriages of their nephews. The realization of the role of the mamak in maintaining the welfare of the family is currently still going well, but the realization of the role of the mamak in the matchmaking of her nephew has now faded due to Islamization and modernization, which will then change the role of the mamak.